1978
DOI: 10.1111/j.1476-5381.1978.tb17321.x
|View full text |Cite
|
Sign up to set email alerts
|

Sympathomimetic Effects of Pancuronium Bromide on the Cardiovascular System of the Pithed Rat: A Comparison With the Effects of Drugs Blocking the Neuronal Uptake of Noradrenaline

Abstract: I The effects of pancuronium bromide on the cardiovascular system of the pithed rat were examined. Pancuronium had two effects, a short-lasting cardiovascular stimulation following injection and a longer-lasting potentiation of responses to sympathetic nerve stimulation. 2 The initial effect of pancuronium was compared with that of tyramine. The cardioaccelerator but not the pressor responses to both pancuronium and tyramine were significantly reduced following sympathectomy with 6-hydroxydopamine (6-OHDA). 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…Pancuronium and gallamine frequently increase heart rate and blood pressure. These changes are explained by cardiac antimuscarinic effects (vagolysis) and sympathetic nervous system stimulation (catecholamine release) following doses adequate to produce skeletal muscle relaxation during surgery (3,4). The hemodynamic changes following d-tubocurarine, pancuronium, gallamine, and occasionally metocurine occur because the muscle-relaxing dose range overlaps the dose range associated with blockade of vagal or sympathetic ganglionic transmission or with histamine release (Fig.…”
Section: Hernodynamic and Autonomic Effectsmentioning
confidence: 97%
“…Pancuronium and gallamine frequently increase heart rate and blood pressure. These changes are explained by cardiac antimuscarinic effects (vagolysis) and sympathetic nervous system stimulation (catecholamine release) following doses adequate to produce skeletal muscle relaxation during surgery (3,4). The hemodynamic changes following d-tubocurarine, pancuronium, gallamine, and occasionally metocurine occur because the muscle-relaxing dose range overlaps the dose range associated with blockade of vagal or sympathetic ganglionic transmission or with histamine release (Fig.…”
Section: Hernodynamic and Autonomic Effectsmentioning
confidence: 97%
“…With this short pulse duration, neuromuscular blockade was not necessary because skeletal muscle twitching was acceptably small. The analysis of sympathetic responses was, therefore, free from the autonomic side-effects associated with muscle relaxants (Docherty & McGrath, 1978). Vascular reactivity was assessed as changes in diastolic blood pressure.…”
Section: Sympathetic Nerve Stimulationmentioning
confidence: 99%
“…Chemical sympathectomy was achieved by pretreating rats with 6-hydroxydopamine (6-OHDA) before pithing: intraperitoneal injections, 2 x 50 mg kg-' on day 1, 2 x I00 mg kg-I on day 4, rats pithed on day 5 or 6 (Thoenen & Tranzer, 1968;Docherty & McGrath, 1978) 6-OHDA was dissolved in de-oxygenated 0.9% w/v NaCl solution (saline) containing ascorbic acid (1 mg kg-').…”
Section: Sympathetic Nerve Stimulationmentioning
confidence: 99%
“…A high level of sympathectomy induced by cervico-thoracic epidural blockade can interrupt sympathetic effects to the heart (10, 1 l ) , while parasympathetic reflexes remain intact. Docherty & McGrath (8) reported that the cardioaccelerator response to pancuronium was reduced following pharmacological sympathectomy with 5-hydroxydopamine in rats, confirming indirect sympathomimetic action of pancuronium.…”
mentioning
confidence: 93%